The Semantic Composition of Basque ’Noun + egin’ predicates - García Murga, Fernado (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2018)
Basque ’Noun + egin’ (’make’) expressions display striking properties for the Grammar of Basque: They have ’defective’ morpho-syntax and semantics, involve discourse opacity, lack scope relations, and show a highly constrained combinatory. These are, however, typical features of (semantic) incorporation structures. A semantic analysis of bare nouns shows that they denote properties. Bounded and unbounded properties will be distinguished. Unbounded properties but not bounded properties project an inherent quantification phrase. This difference explains the distribution of the partitive in ’Noun + egin’ expressions. Given the semantics of their components, the interpretation follows compositional rules. Nonetheless, some idiosyncrasies remain in these structures.